2011
DOI: 10.1111/j.1540-6237.2011.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Descriptive Representation on Latinos' Views of Government and of Themselves*

Abstract: Objective. This article investigates the relationship between descriptive representation and the political attitudes of Latino citizens in the United States. We specifically test the impact of both panethnic and national-origin specific representation on Latino citizens' attitudes toward government and their individual-level identity. Methods. Original data on the ethnicity and national origin of Latino mayors in 2005 and 2006 was merged with the Latino National Survey (2006) to analyze the impact of descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 49 publications
(67 reference statements)
0
37
1
1
Order By: Relevance
“…Many studies examine the impact of majority-minority districts and the descriptive representation they yield (e.g. Monmonier 2001;Dovi 2002;Gay 2002;Tate 2003Tate , 2004Barreto, Segura, and Woods 2004;Rahn and Rudolph 2005;Griffin and Keane 2006;Preuhs 2007;Rocha et al 2010;Sanchez and Morin 2011). While some differences exist, such research suggests that descriptive representation can be empowering and can improve how people feel about their representatives as well as about representative institutions overall.…”
Section: Descriptive Representationmentioning
confidence: 96%
“…Many studies examine the impact of majority-minority districts and the descriptive representation they yield (e.g. Monmonier 2001;Dovi 2002;Gay 2002;Tate 2003Tate , 2004Barreto, Segura, and Woods 2004;Rahn and Rudolph 2005;Griffin and Keane 2006;Preuhs 2007;Rocha et al 2010;Sanchez and Morin 2011). While some differences exist, such research suggests that descriptive representation can be empowering and can improve how people feel about their representatives as well as about representative institutions overall.…”
Section: Descriptive Representationmentioning
confidence: 96%
“…Research on foreign-born Latinos also indicates that their feelings of political alienation increase over time in the United States and are correlated with perceptions of discrimination (Michelson 2001(Michelson , 2003, though these effects can be mitigated by pan-ethnic self-identification (Schildkraut 2005). Moreover, several scholars of Latino politics have found that descriptive representation may also lessen feelings of political alienation (Pantoja and Segura 2003), especially when Latinos are represented by elected officials who share their same national origin (Sanchez and Morin 2011).…”
Section: Political Alienation Efficacy and Trustmentioning
confidence: 99%
“…Our first dependent variable is based on a question that asks respondents to evaluate the role of big interests in government and whether big interests represent people like them. This question is often used as a proxy for political alienation (see Pantoja and Segura 2003;Sanchez and Morin 2011). Secondly, we examine political efficacy directly by utilizing a question asking respondents whether they believe they have a say in government.…”
Section: Methodsmentioning
confidence: 99%
“…7 Linked fate with other Latinos may also augment Latinos' solidarity with African Americans (McClain et al, 2006), over and above the effects of commonality with other Latinos. Linked fate and commonality are normally treated as conceptually distinct (Sanchez & Morin, 2011), in that linked fate predicts group consciousness (McClain et al, 2006), whereas commonality is itself a measure of group consciousness. The two constructs are empirically distinct in the LNS data as well.…”
Section: Other Independent Variablesmentioning
confidence: 99%
“…Hence, in order to provide a more comprehensive understanding of Latino/Black and Latino/White solidarity and to explore the extent that status as measured by national origin shapes Latinos' racial attitudes, we create dummy variables for those of Mexican, Cuban, and Puerto Rican origins. These three groups differ in socioeconomic power and skin tone, are the three largest national origin groups in the United States and in the 2006 LNS, and are commonly used as dummy variables in research using the same data (Sanchez & Morin, 2011). Descriptive summary statistics for all of the independent variables in our models are found in Table A1 in the Appendix.…”
Section: Other Independent Variablesmentioning
confidence: 99%